THE EXECUTION OF THE FEDERAL BUDGET. - Jones, J. Weldon (The Accounting Review, 1942)
Abstract The article presents information about the execution of the Federal Budget of the United States. There are three phases in the development of the budget. (1) The Budget Document is the most comprehensive expression of the work of the U.S. Bureau of the Budget. It is based on the Budget and Accounting Act of 1921 that introduced the executive budget into the system of Federal finances. The Act was a long step forward in bringing order out of chaos. (2) A new landmark in the development of the Budget was the Reorganization Act of 1939, which placed the Bureau of the Budget in the Executive Office of U.S. President. (3) Through the reorganization, the emphasis of the work in the Bureau of the Budget has been shifted from the watchdog function into an instrument of management. The new procedures developed in the present emergency period promise to become a regular instrument of national policy in the future. The U.S. Congress may appropriate for what has been called "developmental programs" extending though a period of years, but leaving the timing of actual expenditures to the Executive, within the framework of the law.